Інформаційний аналіз особливостей структурної перебудови шлуночків серця під впливом хлориду кадмію - Пришляк, А.М.; Гнатюк, М.С.; Стахурська, І.О. (Таврический медико-биологический вестник, 2013)
The heartsof 36 white male rats divided into two groups have been examined by a set of morphological methods: histology, histochemistry, morphometry. The first group included 12 intact animals; the second one consisted of 24 rats to which cadmium chloride was injected. We have analyzed the restructure of the cardiomyocytes of the heartventricles.Under conditions of simulated pathology, the entropy and the relative entropy are increasing and the redundancy is decreasing both inthe left ventricle (by 11,4 %, by 10,5 %, and by a factor of 27 correspondingly) and inright one (by 8,6%, by 6,3%, and by a factor of 1.8 ). The pronounced increase of the entropy and the relative entropy points toinstability and disorganization of the researched structural and functional system (the left and right ventricles). Thus, poisoning of experimental animals with cadmium chloride leads to severere structuring of the left and right ventricles, which is accompanied by significant changes of biological information carriers. At the same time, the entropy and the relative entropy were increasing in the studied chambers of the heart and the redundancy was decreasing, which was indicative of disorganization, instability and reduced adaptation reserves of the damaged structures. The structural changes dominated in the left ventricle. Целью данного исследования стало проведение информационного анализа особенностей структурной перестройки желудочков сердца при воздействии на организм хлорида кадмия. Комплексом морфологических методов (гистология, гистохимия, морфометрия) исследованы сердца 36 белых крыс-самцов, которые были разделены на 2 группы. 1-я группа включала 12 интактных животных, 2-я– 24 крысы, которым вводили хлорид кадмия. Данными информационного анализа структурной перестройки кардиомиоцитов желудочков сердца выявлено, что в условиях смоделированной патологии происходит возрастание энтропии, относительной энтропии и снижение чрезмерности как в левом (на 11,4 %, на 10,5 %, в 2,7 раза соответственно), так и в правом (на 8,6 %, на 6,3 % в 1,8 раза соответственно) желудочках. Выраженное увеличение энтропии и относительной энтропии свидетельствует о нестабильности и дезорганизации исследуемой структурно-функциональной системы (левый, правый желудочки). Следовательно, отравление подопытных животных хлоридом кадмия вызывает выраженную структурную перестройку левого и правого желудочков, которое сопровождается существенным изменением носителей биологической информации. При этом в исследуемых камерах сердца возрастала энтропия, относительная энтропия и снижалась чрезмерность, что свидетельствует про дезорганизацию, нестабильность и снижение резервов адаптации повреждённых структур. Структурные изменения доминировали в левом желудочке.